THE EFFECT OF GREEN ACCOUNTING ON MANUFACTURING FIRM VALUE THROUGH FINANCIAL AND ENVIROMENTAL PERFORMANCE - Natalia, Yessica; Handoko, Jesica (LEMBAGA PENERBIT FAKULTAS EKONOMI DAN BISNIS UNIVERSITAS TRISAKTI, 2026)
Manufacturing companies listed on the Indonesia Stock Exchange are now mandated to prepare sustainability reports as a form of corporate responsibility towards the environment and to meet stakeholder needs. Stakeholders can use reports containing information on the implementation of green accounting to assess firm performance and value. This study aims to analyze the effect of green accounting on firm value, with company performance, including financial and environmental performance, as mediating variables. This study uses manufacturing companies listed on the Indonesia Stock Exchange during the 2021-2023 period. Data were collected through annual reports and company sustainability reports using purposive sampling techniques. From 110 sample companies, data were analyzed using path analysis with the help of SPSS version 25 software. The results show that green accounting positively affects firm value. Financial performance, as measured using Return on Assets (ROA) can mediate the effect of green accounting on firm value, while environmental performance is unable to mediate the relationship. Although investors tend to pay more attention to stock prices that provide financial benefits, this finding indicates that the implementation of green accounting is also an important factor in their decision-making. The mediation of financial performance shows that the implementation of green accounting improves firm performance and firm value. These findings highlight the importance of disclosing the environmental impact of company activities to provide added value to stakeholders.